Relasi Makna Pesan Simbolik dan Tatanan Spasial pada Upacara Penti Masyarakat Kampung Adat Suku Todo - Beyan, Eleonora Vilgia Putri; Herliana, Emmelia Tricia (ARCHIHUMANUM, 2024)
Indonesia has thousands of traditional villages. One of the traditional villages is in Todo Village, West Satar Mese District, Manggarai Regency, East Nusa Tenggara Province. The traditional village, which is known as the Todo Tribe Traditional Village, has a settlement pattern dominated by ritual practices. In this context, culture is a determining factor in the process of forming settlements. The people of the Todo Tribe Traditional Village have maintained this tradition for generations. One of the traditions that is the focus of this research is the annual penti ritual. This ritual is a practice of thanksgiving for the crops carried out by the community. This series of rituals has influenced the uniqueness of this village settlement pattern. This study was conducted qualitatively through a field research. Data collected by interviews and field observation. The analysis uses semiotics, namely the science of signs, so that it can explore and relate the elements of form, function and meaning to the Todo Tribe Traditional Village. Graphical analysis is used to describe and understand the visual aspects of the Todo Tribe Traditional Village which are appropriately presented graphically (charts or pictures). Finally, the existence of the settlement of the Todo Traditional Village is spatially determined by form, function and meaning (verbal and non-verbal symbolic messages).